Co-invading ectomycorrhizal fungal succession in pine-invaded mountain grasslands. (December 2022) - Milani, Tomás; Hoeksema, Jason D.; Jobbágy, Esteban G.; Rojas, J. Alejandro; Vilgalys, Rytas; Teste, François P.
Abstract: Ectomycorrhizal (EM) fungal communities that associate with invading pines ( Pinus spp.) are expected to be poor in species diversity. However, long-term successional trajectories and the persistence of dispersal limitations of EM fungi in the exotic range are not well understood. We sampled the roots and surrounding soil of Pinus elliottii and P. taeda trees invading mountain grasslands of Argentina. We also sampled the EM fungal spore bank in grassland soil near (∼150 m) and far (∼850 m) from the original pine plantations. We found 86 different co-invasive EM fungal OTUs. Differential dispersal capacities among EM fungi were detected in the spore bank of grassland soil, but not under mature pines. After thirty years of invasion, the age, but not the degree of spatial isolation of pine individuals affected the EM fungal composition. We showed how EM fungal succession occurs during pine invasions, which may have clear consequences for ecosystem functioning of co-invaded sites. Highlights: Pines often rely on co-introduced ectomycorrhizal (EM) fungi to invade native ecosystems. EM fungal succession and persistence of dispersal limitations are poorly understood. We found that invading pines can host a highly diverse EM fungal community. The age but not the spatial isolation of pines affected EM fungal composition. Dispersal limitations of EM fungi are only relevant during early pine invasion.